LAW REGULATIONS IN THE SPHERE OF USING GENETICALLY MODIFIED ORGANISMS (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
The article deals with issues connected with pecularities of using genetically modified organisms in agriculture. The author analyses the history of development of legislation undelining law regulations in the sphere of using genetically modified organisms on the international level and in The Russian Federation as well. Different approaches to regulating the production and the sale of genetically modified products are covered in the article.